2011
DOI: 10.1530/joe-10-0420
|View full text |Cite
|
Sign up to set email alerts
|

Insulin treatment attenuates diabetes-increased atherosclerotic intimal lesions and matrix metalloproteinase 9 expression in apolipoprotein E-deficient mice

Abstract: Patients with diabetes mellitus have increased mortality and morbidity of cardiovascular diseases compared with nondiabetic patients. Although clinical studies have shown that effective glycemic control with insulin treatment in patients with type 1 diabetes is associated with reduced cardiovascular events, the underlying mechanisms have not been well understood. In this study, we treated diabetic apolipoprotein E-deficient (apoEK/K) mice with insulin for 20 weeks and studied the effect of insulin treatment on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…Previous studies reported that the expression of MMP-9 is increased in atherosclerotic plaques from diabetic patients and that insulin treatment reduces MMP-9 tissue expression as well as its secretion by macrophages. 30 Moreover, we observed that M1 macrophages from diabetic patients also displayed a more important proangiogenic activity (increased VEGF/TFPI-2 and TF/TFPI-2 ratios) compared to non-diabetic patients. Our histological and in vitro results could explain the link between increased number of microvessels and plaque vulnerability observed in diabetic patients.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies reported that the expression of MMP-9 is increased in atherosclerotic plaques from diabetic patients and that insulin treatment reduces MMP-9 tissue expression as well as its secretion by macrophages. 30 Moreover, we observed that M1 macrophages from diabetic patients also displayed a more important proangiogenic activity (increased VEGF/TFPI-2 and TF/TFPI-2 ratios) compared to non-diabetic patients. Our histological and in vitro results could explain the link between increased number of microvessels and plaque vulnerability observed in diabetic patients.…”
Section: Discussionmentioning
confidence: 63%
“…1C). In addition, the content of MMP-9, which was mainly secreted by macrophages and known to be involved in plaque destabilization [22,23], was lowered in H 2 -or simvastatin-treated mice (Fig. 1D and E).…”
Section: H 2 Increases Atherosclerotic Plaque Stability In Ldlr à / àmentioning
confidence: 93%
“…In this regard, insulin also has the potential to inhibit MMP-9 activity and protect endothelial cells in subacute arterial injury 36 or in atherosclerotic intimal lesions of diabetic apolipoprotein E-deficient (apoE −/− ) mice. 37 However, it is still controversial whether insulin-mediated reduction in blood glucose in acute hyperglycemia during ischemic stroke represents an effective intervention. 10 Moreover, caution must be used when attempting to achieve euglycemic control with insulin treatment because of the risk of hypoglycemia.…”
Section: Strokementioning
confidence: 99%